Choroid plexus involvement in dogs with spontaneous visceralleishmaniasis - Melo, Guilherme D.; Machado, Gisele F. (Brazilian Journal of Veterinary Pathology, 2009)
Visceral leishmaniasis is associated with chronic inflammatory stimulation, resulting in different clinical manifestations, ranging from unapparent infection to a systemic disease. In dogs, there are descriptions of neurological involvement with inflammatory infiltrates and specific antibodies in cerebrospinal fluid. To investigate the involvement of the choroid plexus and the blood-CSF barrier during the infection, we describe the morphological alterations in the choroid plexi of dogs naturally infected by Leishmania (Leishmania) chagasi. A total of 44 mixed-breed adult dogs were selected from the Veterinary Hospital of UNESP-Araçatuba and from the Zoonosis Control Center in Araçatuba, São Paulo State, Brazil. This area is endemic for canine visceral leishmaniasis. Routine ELISA tests and cytological examination of a tissue smear of the popliteous lymph node were proceeded to diagnose Leishmania infection. During the necroscopic examination, the brain was collected and samples containing the choroid plexi were stored in 10% buffered formalin and subjected to histological procedures, following staining with haematoxylin–eosin, Congo red and Masson’s trichromic. The dogs were classified in three experimental groups: symptomatic dogs (n=11), oligosymptomatic dogs (n=21) and uninfected dogs (n=12). The choroid plexi of symptomatic and oligosymptomatic dogs presented a chronic inflammatory reaction with lymphoplasmacytic infiltrate in higher intensity than the control dogs (P=0.0044). These findings give additional support to confirm that the choroid plexus is an important mediator between periphery and the brain, and that the choroid plexus acts as pathway to initiate an inflammatory process within the nervous tissue in visceral leishmaniasis.